Local and geographical factors jointly drive elevational patterns in three microbial groups across subarctic ponds - Teittinen, Anette; Wang, Jianjun; Stromgard, Simon; Soininen, Janne (Global Ecology and Biogeography, 2017)
Aim: Elevational biodiversity patterns are understudied in high-latitude aquatic systems, even though these systems are important for detecting very early impacts of climatic changes on Earth. The aim of this study was to examine the elevational trends in species richness and local contribution to beta diversity (LCBD) of three biofilm microbial groups in freshwater ponds and to identify the key mechanisms underlying these patterns. Location: One hundred and forty-six ponds in subarctic Finland and Norway distributed across the tree line along an elevational gradient of 10-1,038 m a.s.l., spanning from forested landscape to barren boulder fields. Time period: July-August 2015. Major taxa studied: Diatoms, cyanobacteria and non-cyanobacteria. Methods: Generalized linear models were used to identify the most important pond variables explaining richness and LCBD. Structural equation models were used to explore the direct and indirect effects of multiscale drivers on richness and LCBD. Results: Diatom and cyanobacteria richness showed unimodal elevational patterns, whereas non-cyanobacteria richness decreased with increasing elevation. The LCBD-elevation relationship was U-shaped for all three microbial groups. Diatom and cyanobacteria richness and LCBD were best explained by local pond variables, especially by pH. Non-cyanobacteria richness and LCBD were related to pond variables, elevation as a proxy for climatic conditions, and normalized difference vegetation index as a proxy for terrestrial productivity. Main conclusions: Aquatic autotrophs were primarily controlled by environmental filtering, whereas heterotrophic bacteria were also affected by terrestrial productivity and elevation. All studied aspects of microbial diversity were directly or indirectly linked to elevation; therefore, climatic changes may greatly alter aquatic microbial assemblages. Peer reviewed